Methylene Blue Dye Adsorption from Wastewater Using Hydroxyapatite/Gold Nanocomposite: Kinetic and Thermodynamics Studies - Sharma, Kashma; Sharma, Shreya; Sharma, Vipasha; Mishra, Pawan Kumar; Ekielski, Adam; Sharma, Vishal; Kumar, Vijay (Nanomaterials (Basel, Switzerland), 2021)
The present work demonstrates the development of hydroxyapatite (HA)/gold (Au) nanocomposites to increase the adsorption of methylene blue (MB) dye from the wastewater. HA nanopowder was prepared via a wet chemical precipitation method by means of Ca(OH)2 and H3PO4 as starting materials. The biosynthesis of gold nanoparticles (AuNPs) has been reported for the first time by using the plant extract of Acrocarpus fraxinifolius. Finally, the as-prepared HA nanopowder was mixed with an optimized AuNPs solution to produce HA/Au nanocomposite. The prepared HA/Au nanocomposite was studied by using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and Scanning Electron Microscopy (SEM) with Energy Dispersive X-Ray Analysis (EDX) analysis. Adsorption studies were executed by batch experiments on the synthesized composite. The effect of the amount of adsorbent, pH, dye concentration and temperature was studied. Pseudo-first-order and pseudo-second-order models were used to fit the kinetic data and the kinetic modeling results reflected that the experimental data is perfectly matched with the pseudo-first-order kinetic model. The dye adsorbed waste materials have also been investigated against Pseudomonas aeruginosa, Micrococcus luteus, and Staphylococcus aureus bacteria by the agar well diffusion method. The inhibition zones of dye adsorbed samples are more or less the same as compared to as-prepared samples. The results so obtained indicates the suitability of the synthesized sample to be exploited as an adsorbent for effective treatment of MB dye from wastewater and dye adsorbed waste as an effective antibacterial agent from an economic point of view.
Keywords: antibacterial; hydroxyapatite; nanocomposites; dye adsorbed waste; dye adsorption; gold nanoparticles